Herbaceous competition and browsing may induce arrested succession in central European forests. (13th November 2017) - Thrippleton, Timothy; Bugmann, Harald; Snell, Rebecca S.
Abstract: Arrested succession, that is, an ecosystem permanently halted in an early successional, typically non‐forested state, has been suggested to result from intense competition by understorey vegetation, high browsing pressure and additional disturbances, but the relative importance of these factors is unclear. In addition, distinguishing between permanently arrested succession or merely delayed succession may be highly challenging, if not impossible, due to the large time‐scales involved. We used the dynamic vegetation model LandClim to systematically explore the effect of multiple factors on delayed and arrested succession over a time span of 1, 000 years, starting from an unforested state. We included abiotic and biotic factors as well as large‐scale overstorey disturbance, in four Central European landscapes. Arrested succession occurred in 1%–14% of the simulations. Among the non‐arrested simulations, 95% reached a forested state (defined as ≥10% canopy cover) within 100 years. Large herbaceous biomass was the most important predictor for arrested succession, followed by browsing and large‐scale disturbances. Combinations of factors were important at particular locations in the landscape, where understorey competition and browsing jointly induced a strong establishment filter. Abiotic conditions consistently influenced the probability of arrested succession, with a low probability under mesic conditions and increased likelihood in more xeric parts of the landscapes. Synthesis . We demonstrated that permanently arrested succession has the potential to occur in temperate forests, particularly under a combination of high amounts of herbaceous biomass and ungulate browsing in drought‐constrained landscape positions. We thus conclude that considering environmental heterogeneity at the landscape scale is key for understanding the conditions that lead to delayed and arrested succession. Abstract : We demonstrate that permanently arrested succession has the potential to occur in temperate forests, particularly under a combination of high amounts of herbaceous biomass and ungulate browsing in drought‐constrained landscape positions. We thus conclude that considering environmental heterogeneity at the landscape scale is key for understanding the conditions that lead to delayed and arrested succession.